2017 IEEE Intelligent Vehicles Symposium (IV) 2017
DOI: 10.1109/ivs.2017.7995812
|View full text |Cite
|
Sign up to set email alerts
|

Scale optimization for full-image-CNN vehicle detection

Abstract: Many state-of-the-art general object detection methods make use of shared full-image convolutional features (as in Faster R-CNN). This achieves a reasonable test-phase computation time while enjoys the discriminative power provided by large Convolutional Neural Network (CNN) models. Such designs excel on benchmarks 1 which contain natural images but which have very unnatural distributions, i.e. they have an unnaturally high-frequency of the target classes and a bias towards a "friendly" or "dominant" object sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 22 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…They found that a pre-trained Faster R-CNN ResNet model fine-tuned with 700 CCTV images could identify more small vehicles in the image background, providing better precision and fewer false negatives than the fine-tuned SSD model. To address the issue of varying vehicle scales in a natural scene, the study in [ 32 ] optimized the default anchor box size and changed the default combination of convolutional layers in the Faster R-CNN architecture using KITTI image datasets. That way, they further improved its performance in detecting small vehicles by circa 7%.…”
Section: Related Workmentioning
confidence: 99%
“…They found that a pre-trained Faster R-CNN ResNet model fine-tuned with 700 CCTV images could identify more small vehicles in the image background, providing better precision and fewer false negatives than the fine-tuned SSD model. To address the issue of varying vehicle scales in a natural scene, the study in [ 32 ] optimized the default anchor box size and changed the default combination of convolutional layers in the Faster R-CNN architecture using KITTI image datasets. That way, they further improved its performance in detecting small vehicles by circa 7%.…”
Section: Related Workmentioning
confidence: 99%
“…Ye Wang [11] optimized anchor generation and improved performance through region of interest allocation, making the number of features after pooling more suitable for final prediction. Yang Gao et al [12] improved the convolution layer region scheme of the Faster R-CNN model and improved the detection accuracy by 7.3% through the KITTI data test. Reference [13] presents a pre-processing pipeline on Faster R-CNN to improve the training and detection speed.…”
Section: Introductionmentioning
confidence: 99%
“…2018, 10, 131 2 of 21 (CNN), several design variations using region based CNN have generated the state-of-the-art performance against traditional multi-class object detection benchmarks [16][17][18][19][20]. These benchmark datasets typically present target objects with "friendly" or dominant scales because those images in a large pool of available images and objects with significant scales, could be more easily selected [21]. Unlike objects on these benchmark datasets, objects on HRS images are much smaller, including fixed shape objects (e.g., airplanes, ships, vehicles, etc.)…”
Section: Introductionmentioning
confidence: 99%